Reply [to "The comfort and effectiveness of hearing protection devices"] - Arezes, P. (2003)
Reply letter to Edwards, 2003, which has sent a letter to editor regarding a previous paper on hearing protection acceptability, published on Ann. Occup. Hyg., vol. 47, nr. 4, p. 337 (2003).